Iron and Steel Industry: A Suggestion for Raw Materials in Libya - Osama Shaltami,; Firas Khamis,; Kamal Abraheem,; Mustafa Ben Hkoma, (AlQalam Journal of Medical and Applied Sciences, 2025)
The iron and steel industry is arguably the most significant component of a country's industrial economic infrastructure, and the amount of steel consumed per person serves as a proxy for both industrialization and advancement. There are two processes in the extraction of ferrous metals: (1) the Ironmaking process (reduction process); and (2) the Steelmaking process (oxidation process). This study aims to suggest uses for Libyan iron ores in the iron and steel industry. The study covered thirteen areas (Sabkhat Ghuzayil, Al Fuqaha, Sabha, Tanahmu, Idri, Qararat Al Marar, Hasi Anjiwal, Bir Anzawa, Tikiumit, Al Awaynat, Wadi Tanezzuft, Anay, and Ghat sheets). This work can be regarded as the first of its kind because no previous study has been done on the raw materials used in the iron and steel industry in Libya. Numerous formations have been found to contain iron ore (Hasawnah Formation, Melaz Suqran Formation, Tanezzuft Formation, Akakus Formation, Tadrart Formation, Wan Kasa Formation, Awainat Wanin Formation, Marar Formation, Zarzaitine Formation, Taouratine Formation, Mesak Formation, Al Hishah Formation, Old wadi deposits, and sabkha sediments). Given that the results showed that the Fe concentrations in the studied sediments ranged from 15.21 to 54.53%, it is feasible to use these sediments in the iron and steel industry.